1999
DOI: 10.1300/j069v18n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Initial Exposure to Nicotine in College-Age Women Smokers and Never-Smokers

Abstract: Recent research suggests that people who become smokers may be more sensitive to the positive effects of nicotine upon initial exposure than those who do not take up smoking. The present study was designed to extend these findings to a sample of college-age women never-smokers and light smokers. Subjects were asked to rate pleasurable and displeasurable sensations upon first smoking and to indicate the presence or absence of pleasurable rush or buzz, relaxation, dizziness, nausea, and cough. Pleasurable sensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 11 publications
7
53
1
2
Order By: Relevance
“…Consistent with other reports in the literature ( Chen et al, 2003 ;DiFranza et al, 2004 ;Hahn et al, 1990 ;Pomerleau et al, 1998Pomerleau et al, , 1999Wang, Fitzhugh, Trucks, Cowdery, & Perko, 1995 ), pleasurable sensations upon early experiences with smoking were identifi ed as an important factor in the transition from experimentation to regular cigarette use. These early pleasant experiences do not exclude the concomitant experience of unpleasant sensations, but our fi ndings suggest that the absence of unpleasant sensations cannot be ruled out as an additional contributing factor that facilitates the transition to smoking in vulnerable individuals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with other reports in the literature ( Chen et al, 2003 ;DiFranza et al, 2004 ;Hahn et al, 1990 ;Pomerleau et al, 1998Pomerleau et al, , 1999Wang, Fitzhugh, Trucks, Cowdery, & Perko, 1995 ), pleasurable sensations upon early experiences with smoking were identifi ed as an important factor in the transition from experimentation to regular cigarette use. These early pleasant experiences do not exclude the concomitant experience of unpleasant sensations, but our fi ndings suggest that the absence of unpleasant sensations cannot be ruled out as an additional contributing factor that facilitates the transition to smoking in vulnerable individuals.…”
Section: Discussionsupporting
confidence: 85%
“…Retrospective reports of early smoking experiences, though theoretically a source of bias and not universally validated (see, e.g., Riedel, Blitstein, Robinson, Murray, & Klesges, 2003 ), have been well supported in the literature, with repeated demonstrations of enhanced sensitivity in young smokers in the United States and elsewhere, indicating that the early-experience reports do not simply refl ect selective recall of positive experiences by current smokers ( Chen et al, 2003 ;DiFranza et al, 2004 ;Pomerleau et al, 1999 ). Studies of early experiences as well as other aspects of smoking behavior suggest that self-report of tobacco use is generally reliable ( Brigham et al, 2008 ;Hudmon, Pomerleau, Brigham, Javitz, & Swan, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The symptom of dizziness is considered both a pleasant and unpleasant symptom (Rios-Bedoya, Pomerleau, Neuman, & Pomerleau, 2009). Prior studies suggest that pleasant experiences in response to early experimentation with smoking lead to regular smoking and that pleasant experiences play a stronger role than unpleasant experiences in the transition to regular smoking (Pomerleau, Pomerleau, & Namenek, 1998;Pomerleau, Pomerleau, Namenek, & Marks, 1999;Pomerleau et al, 1993;Rios-Bedoya et al, 2009). Recently, Haberstick, Ehringer, Lessem, Hopfer, and Hewitt (2011) reported that initial reactions to cigarettes are due to both heritable contributions and unique environmental experiences, and in line with this finding, Sherva et al (2008) found an association between a genetic variant in CHRNA5 and enhanced pleasurable responses to initial cigarette use in regular smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Among adults, retrospective reports of the rewarding effects of the initial smoking experience (e.g., pleasurable rush or buzz, relaxation) were associated with current levels of nicotine dependence (Pomerleau, 1998). These findings were replicated recently in a sample of college-age women (Pomerleau et al, 1999).…”
Section: Reinforcing Properties Of Nicotinementioning
confidence: 72%